Expression of a unique M. tuberculosis DNA MTase Rv1509 in M. smegmatis alters the gene expression pattern and enhances virulence - Manjunath, P.; Ahmad, Javeed; Samal, Jasmine; Rani, Anshu; Sheikh, Javaid Ahmad; Zarin, Sheeba; Ahuja, Yashika; Alam, Anwar; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Microbiology, 2024)
Mycobacterium tuberculosis (M. tb) genome encompasses 4,173 genes, about a quarter of which remain uncharacterized and hypothetical. Considering the current limitations associated with the diagnosis and treatment of tuberculosis, it is imperative to comprehend the pathomechanism of the disease and host-pathogen interactions to identify new drug targets for intervention strategies. Using in-silico comparative genome analysis, we identified one of the M. tb genes, Rv1509, as a signature protein exclusively present in M. tb. To explore the role of Rv1509, a likely methyl transferase, we constructed a knock-in Mycobacterium smegmatis (M. smegmatis) constitutively expressing Rv1509 (Ms_Rv1509). The Ms_Rv1509 led to differential expression of many transcriptional regulator genes as assessed by RNA-seq analysis. Further, in-vitro and in-vivo studies demonstrated an enhanced survival of Ms_Rv1509 inside the host macrophages. Ms_Rv1509 also promoted phagolysosomal escape inside macrophages to boost bacterial replication and dissemination. In-vivo infection studies revealed that Ms_Rv1509 survives better than BCG and causes pathological manifestations in the pancreas after intraperitoneal infection. Long-time survival of Ms_Rv1509 resulted in lymphocyte migration, increased T regulatory cells, giant cell formation, and likely granuloma formation in the pancreas, pointing toward the role of Rv1509 in M. tb pathogenesis.